Anti-Tumor Necrosis Factor-Alpha Withdrawal in Children With Inflammatory Bowel Disease in Endoscopic and Histologic Remission. Issue 2 (9th April 2021) - Scarallo, Luca; Bolasco, Giulia; Barp, Jacopo; Bianconi, Martina; di Paola, Monica; Di Toma, Michele; Naldini, Sara; Paci, Monica; Renzo, Sara; Labriola, Flavio; De Masi, Salvatore; Alvisi, Patrizia; et al.
Abstract: Background: The aim of the present study was to investigate outcomes of anti-TNF-alpha (ATA) withdrawal in selected pediatric patients with inflammatory bowel disease who achieved clinical remission and mucosal and histological healing (MH and HH). Methods: A retrospective analysis was performed on children and adolescents affected by Crohn disease (CD) and ulcerative colitis (UC) who were followed up at 2 tertiary referral centers from 2008 through 2018. The main outcome measure was clinical relapse rates after ATA withdrawal. Results: One hundred seventy patients received scheduled ATA treatment; 78 patients with CD and 56 patients with UC underwent endoscopic reassessment. We found that MH was achieved by 32 patients with CD (41%) and 30 patients with UC (53.6%); 26 patients with CD (33.3%) and 22 patients with UC (39.3%) achieved HH. The ATA treatment was suspended in 45 patients, 24 affected by CD and 21 by UC, who all achieved concurrently complete MH (Simplified Endoscopic Score for CD, 0; Mayo score, 0, respectively) and HH. All the patients who suspended ATA shifted to an immunomodulatory agent or mesalazine. In contrast, 17 patients, 8 with CD and 9 with UC, continued ATA because of growth needs, the persistence of slight endoscopic lesions, and/or microscopic inflammation. Thirteen out of 24 patients with CD who suspended ATA experienced disease relapse after a median follow-up time of 29 months, whereas no recurrence was observed among the 9 patients with CD who continued treatment ( P = 0.05). Among the patients with UC, there were no significant differences in relapse-free survival among those who discontinued ATA and those who did not suspend treatment ( P  = 0.718). Conclusions: Despite the application of rigid selection criteria, ATA cessation remains inadvisable in CD. In contrast, in UC, the concurrent achievement of MH and HH may represent promising selection criteria to identify patients in whom treatment withdrawal is feasible.